Analysis of Patients Undergoing Surgical Treatment for Primary Spontaneous Pneumothorax - Cakmak, M.; Durkan, A. (Wolters Kluwer Medknow Publications, 2021)
Background: Primary spontaneous pneumothorax (psp) results from spontaneous rupture of bleb or bulla. Aims: We planned to discuss the etiologic factors, clinical and radiological findings, and treatment results of psp cases. Materials and Methods: 402 patients were evaluated. Patients were divided into two groups as patients receiving positive results with thoracostomy and patients who received positive results thoracotomy/video-assisted thoracoscopic surgery (vats). Groups were compared. Results were evaluated using Chi-square or Fishers' exact test. P < 0.05 was considered as significant. Results: Gender difference (P: 1.00) and localization of disease (P: 0.45) were not significant for psp. Smoking and being subtotal or total compared to partial had a substantial effect on the implementation of thoracotomy/vats (P < 0.05). Furthermore, psp was most frequently seen in August and September. Discussion: Risk factors of psp are described as genetic predisposition, being tall, smoking, and autosomal dominant heredity. The main determinant factor in the treatment of psp is the degree of pneumothorax. Conclusion: Psp was frequently observed in smokers. The preferred method for overall psp is tube thoracostomy. Thoracotomy/vats is more commonly performed for subtotal or total psp compared to partial psp.
Keywords: Pneumothorax; spontaneous; thorcrcostomy; thoracotomy